Theoretical Design for the Non-Toxic and Earth-Abundant Perovskite Solar Cell Absorber Materials - Feng, Chunbao; Feng, Guanghui; Zhao, Qing; Li, Shichang; Li, Dengfeng (Frontiers in Materials, 2020)
Though the perovskite solar cells have good prospects, there are also some shortcomings, especially the impact of Pb on the environment and the use of expensive elements make it difficult to industrialize. Using first-principle density functional theory, we have investigated the geometry structures, electronic structures and optical absorption coefficients of the non-toxic and earth-Abundant 1B-based perovskite solar cells absorbers. Our results show that Cs2AgAuI6, a toxic-free and inexpensive AgAu-based perovskite solar cell absorbers, is a suitable one. It has a proper HSE band gap (1.289eV) and a sharp absorption coefficient (~105 cm-1). Meanwhile, it is beneficial to the average effective mass of electron and hole carrier, 0.346m0 and 0.316m0, respectively. The phonon spectra show that it is stable. Because Cu d-orbital energy is higher than that of Ag and Au, CuAu-based perovskite is not stable. This can be seen from the phonon spectra. Therefore, our calculations could provide strong evidence for the experimental to synthesis the lead-free and low-cost perovskite solar cell absorber materials.